A new mouse model of ankle instability induced by multiple mechanical sprains with controlled inversion angle and speed - Ching, Shih-Hong; Chiu, Yen-Chun; Liao, Yu-Ching; Yang, Shang-Hsun; Tsai, Yi-Ju (Frontiers in Bioengineering and Biotechnology, 2022)
Ankle sprain occurs by a sudden and extreme inversion and plantarflexion at the ankle joint to cause ligamentous injuries. A portion of ankle sprain patients experience recurrent ankle sprains and develop chronic ankle instability (CAI). The present CAI animal models are single events with severe ligamentous injury using surgical transection of ligaments or manually overextending the ankle. Purpose: To simulate the mechanical and recurrent sprain injuries in CAI patients, we established a new ankle instability model with multiple ankle injuries using a self-designed machine to sprain the ankle with a controlled inversion angle and speed. Methods: Male C57BL/6J mice were used and respectively subjected to a sham operation, calcaneofibular ligament (CFL) transection, and mechanical ankle sprains. Three mechanical sprains were performed on the 13th and 185th day after the initial mechanical ankle sprain. Results: The first mechanical sprain and CFL transection induced ankle injury as indicated by an average of a 62% decrease in ankle pressure pain threshold and a 114% increase in the ankle thickness compared with the contralateral untreated ankle. The second and third mechanical sprains induced recurrent ankle injuries. The foot slips during beam tests were increased after mechanical ankle sprains but not after CFL transection, indicating the induction of motor balance deficits. Multiple mechanical ankle sprains induced significant gait changes in longer duration of stance (an average of 194% increase), swing (134%), and step cycle (147%) compared with CFL transection or sham operation, and slower walking speed (78% reduction) and shorter step distance (91%) after the third sprain. Conclusion: These results elucidate that multiple mechanical sprains, which induce recurrent ankle injuries, balance deficits, and gait changes, are a good model for investigating the mechanisms of CAI induced by recurrent sprain injuries.